Signals and genes driving mixed community biofilm formation - Muhammad Zulfadhly Mohammad Muzaki (Nanyang Technological University, 2022)
Most studies on the signals and mechanisms of biofilm formation to date have focused on single-species biofilms. However, biofilms in natural environments such as dental plaques, cystic fibrosis lungs and streams often exist as mixed-species biofilm communities. Due to the adverse impacts of biofilms in chronic infections and the potential industrial applications of biofilms such for bioremediation, it is important to understand the interspecies interactions and signals that shape these mixed-species biofilm communities. Here, an experimental mixed-species biofilm community consisting of Pseudomonas aeruginosa PAO1, Pseudomonas protegens Pf5 and Klebsiella pneumoniae KP-1/MGH78578 was studied to determine how the signals and interspecies interactions within the community affect the structure, spatial organization, composition and antimicrobial resistance of the biofilm community.